The Values of Entrepreneurship in “Chopsticks” Economies : An Individual-Based Analysis on Entrepreneurship Values - Koay, Cheow Khoon (2015)
For several decades, the “Chopstick” economies have been experiencing tremendous growth and have been very robust in withstanding several waves of financial crises. The strength of the economies could be attributed to its culture and entrepreneurial spirit in the region. Thus, samples from the World Value Survey is extracted and explained using the Schwartz Theory to find out the values that are important to the “Chopstick” entrepreneurs. Multiple sources of literature ranges from business journals to psychology journals were used to form the assumption about the “Chopsticks” societies, the entrepreneurs and on-entrepreneurs, as well as the different demographic groups of entrepreneurs within the societies. Since this is a cross countries analysis, a quantitative analysis was used on the World Value Survey database to check the value priorities and value differences among the sample groups. The result is then compared and discussed against the assumption cantered around the literature. Interestingly, the result shows some consistencies with the values shared by vast majority of nations reported by Schwartz. However, the “Chopsticks” societies and their entrepreneurs seem to value security more. The consistencies in value priorities among the entrepreneur groups and non-entrepreneur groups are believed to be influenced mainly by the Confucianism culture, although political,economics and other institutional forces also play a part in shaping individual’s values. Lastly, the discussion of the finding is followed by conclusion and recommendation to inculcate values that are more conducive for entrepreneurship around the region.